THE EVALUATION OF LOCO-REGIONAL ANESTHESIA ACCIDENTS AND COMPLICATIONS IN ORAL AND MAXILLOFACIAL SURGERY - Ciprian Roi; Alexandra Roi; Laura-Cristina Rusu; Mircea Riviș (Romanian Society of Oral Rehabilitation, 2023)
Current medical concerns lead to painless and anxiety-free surgical treatment from the time of anesthesia to the completion of therapeutic surgery. Loco-regional anesthesia is widely used for oral and maxillofacial surgical procedures due to the advantages com-pared to the general anesthesia: the collaboration with the patient is maintained during the surgical procedure, the localized anesthesia in the operatory field, the general side-effects and allergic risks are maintained on a minimum level the resumption of patient feeding as soon as the anesthesia is metabolized. On the other hand, the accidents, and the complications of the loco-regional anesthesia in oral and maxillofacial surgery were insufficient studied. Our study is the first one which highlights these aspects and brings a new point of view for understanding the most common and the rarest ones. In this prospective observational study were included 100 patients which presented for different oral and maxillofacial surgical interventions under loco-regional anesthesia. All the anesthesia accidents and complications were noted and discussed. Loco-regional anesthesia remains the safest and most used type of anesthesia in oral and maxillofacial surgery. The accidents and complications can be prevented by knowing local anatomy, pharmacological properties of anesthetic substances and patient comorbidities.